2015
DOI: 10.3171/2014.12.jns141077
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of neurosurgical reoperations: use of a surgical checklist and reduction of infection-related and preventable complication-related reoperations

Abstract: OBJECT Use of the WHO surgical checklist has been proven to reduce surgical morbidity and mortality, but its effect on surgical complications requiring reoperation has not been previously studied. The aim of this study was to determine whether the use of the WHO surgical checklist would have an impact on the number and causes of neurosurgical complications leading to a reoperation. METHODS The authors retrospectively gathered information on all neurosurgical reoperations using hospital discharge data as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Although several investigators have challenged the efficacy of the SSC, it has shown repeated success in reducing preventable postoperative complications, length of hospital stay, and overall mortality [18,[37][38][39]. In addition, multiple investigators have concluded that the implementation of the SSC in multiple institutions has improved communication, efficiency, and attention to routine details in the operating room.…”
Section: Preventive Measures To Improve Safety: the Who Surgical Safementioning
confidence: 99%
“…Although several investigators have challenged the efficacy of the SSC, it has shown repeated success in reducing preventable postoperative complications, length of hospital stay, and overall mortality [18,[37][38][39]. In addition, multiple investigators have concluded that the implementation of the SSC in multiple institutions has improved communication, efficiency, and attention to routine details in the operating room.…”
Section: Preventive Measures To Improve Safety: the Who Surgical Safementioning
confidence: 99%
“…A comprehensive literature search on reoperations in neurosurgery revealed only 4 studies on the topic, 5,6,8,9 with no studies specifically examining 48-hour reoperation rates.…”
Section: Reoperations In Neurosurgerymentioning
confidence: 99%
“…T hirTy-day readmission and reoperation rates have been used as quality indicators across surgical specialties. 1,2,[4][5][6][8][9][10][11][12]14 This relatively long time interval (30 days) enables one to capture complications resulting from complex interplays among preoperative, intraoperative, and postoperative factors following the index surgery. For example, surgical infection could be a direct result of breaches of proper sterile technique, but it could also result from poor wound care or lack of access to medical care.…”
mentioning
confidence: 99%
“…Favourable patient outcomes were associated with the use of WHO SSC in several studies with reductions in complications 10,19,92,[94][95][96][97][98][99][100][101][102][103][104] , mortality 10,11,62,88,94,102,105,106 , unplanned reoperations 10,19,99,107 , and unplanned readmissions 91,98,108 , LOS 19,89,105,106 , while other studies reported no significant changes after introduction of the WHO SSC as to complications 89,93,106,[109][110][111][112][113][114] , mortality 19,89,91,93,95,[97][98][99]…”
Section: Re-admission Los Othersmentioning
confidence: 99%
“…Our updated review (table 1, page 13) found several original studies reporting reductions in reoperations with WHO SSC use 10,19,87,107 , but also studies reporting no such effects 89, 92, 97-99, 101, 111 . All studies, except one 107 , reported on reoperations as a sub-analysis, and not as a main outcome.…”
Section: Effects On Patient Outcome Of Adding the Surpass Checklists mentioning
confidence: 99%